The subject's point of view - Farkas, Katalin (Oxford : Oxford University Press, 2008)
Katalin Farkas comes to the defence of a Cartesian view of the mind. She argues that Descartes' influence is more beneficial and his conception of the mind more deeply rooted in our understanding of ourselves, than most philosophers allow.
Description based on print version record.
Includes bibliographical references and index.
Keywords: d; Philosophy of mind; Externalism (Philosophy of mind); Internalism (Theory of knowledge); Knowledge, Theory of